If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -16 + -3x = 5x + -9 Reorder the terms: -16 + 6x + -3x = 5x + -9 Combine like terms: 6x + -3x = 3x -16 + 3x = 5x + -9 Reorder the terms: -16 + 3x = -9 + 5x Solving -16 + 3x = -9 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -16 + 3x + -5x = -9 + 5x + -5x Combine like terms: 3x + -5x = -2x -16 + -2x = -9 + 5x + -5x Combine like terms: 5x + -5x = 0 -16 + -2x = -9 + 0 -16 + -2x = -9 Add '16' to each side of the equation. -16 + 16 + -2x = -9 + 16 Combine like terms: -16 + 16 = 0 0 + -2x = -9 + 16 -2x = -9 + 16 Combine like terms: -9 + 16 = 7 -2x = 7 Divide each side by '-2'. x = -3.5 Simplifying x = -3.5
| 2-b+7b-2= | | 8.9y-7.35=12.4y | | 3-6x=-2x-37 | | 6+.10x=0.15x+8 | | -7x+7(-3x+18)=-14 | | 15h-11h=20 | | 1.25n=4 | | -5/6+x=11/6 | | -5=(x+9) | | 12x+14+10v=80 | | 36/x-8=6/7 | | 5x-9=-3x-25 | | x/5-13=22 | | y=7/8(0)+5y | | 6x+2(6x-3)=-144 | | 2x-2x/7=x/2+17/2 | | 16x+1=-14 | | 2(x+10)=x-7 | | -5(w+5)= | | -6x-76=98-12x | | -1+6x=3x-19 | | (27p^6)^(5/3) | | -6-k+2-5k= | | 8x-2(x-8)=6(x+1)+7 | | 5-10t=-25 | | 40=5x+2(-x+2) | | x^2-23x=3 | | -2y+9-y=-7y-7 | | y/6-4=6 | | z/5-6=2/1/6 | | -15h-8.8h-20=20-19.8h | | 12g-3g--9g=-18g |